2003
DOI: 10.1111/1467-6486.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Significance of Strategic Episodes: Social Systems Theory and the Routine Practices of Strategic Change

Abstract:  In this paper we draw on Niklas Luhmann's social systems theory, and in particular his concept of an 'episode', to guide research into strategic practice and its relationship to the operating routines of an organization. Episodes, in Luhmann's theory, provide a mechanism by which a system can suspend its routine structures and so initiate a reflection on and change of these structures. Applying this theory to the organizational process of strategic change, we draw attention to the routine nature of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
290
0
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 320 publications
(323 citation statements)
references
References 27 publications
7
290
0
26
Order By: Relevance
“…In our study, we actually did observe strategic changes as a result of workshop activities. We would argue that in the specific case of a series of strategy workshops, the effectiveness paradox can be circumvented: such series appear to separation and reconnection to occur over the course of several workshops and seem also to create opportunities for strategic episodes (Hendry and Seidl, 2003) to transfer to the wider organization. This is in line with the study of Schwarz and Balogun (2007), who also reported on series of workshops.…”
Section: Discussion and Contributionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, we actually did observe strategic changes as a result of workshop activities. We would argue that in the specific case of a series of strategy workshops, the effectiveness paradox can be circumvented: such series appear to separation and reconnection to occur over the course of several workshops and seem also to create opportunities for strategic episodes (Hendry and Seidl, 2003) to transfer to the wider organization. This is in line with the study of Schwarz and Balogun (2007), who also reported on series of workshops.…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…Such processes effectively challenge organisation members to reconsider the identity of their organisation (Beech 2000). This process requires a comparatively safe environment and Hendry and Seidl (2003) argue that the renegotiation of such fundamental assumptions occurs in the course of 20 "episodes", such as workshops, where customary practices are suspended. Such episodes make it possible for the members of an organisation to step out of their daily routines in order to reflect on them critically (Doz and Prahalad 1987;Roos and Von Krogh 1996).…”
Section: Discussion and Contributionmentioning
confidence: 99%
See 3 more Smart Citations